The sizzle paradox - Menon, Lily (St. Martin's Griffin, 2022)
"The Kiss Quotient meets Love Potion No. 9 in the next sparkling romantic comedy by Lily Menon, The Sizzle Paradox. Lyric Bishop feels like a fraud - she's studying sexual chemistry in romantic partners and what makes for a successful long-term relationship, only she can't seem to figure it out in her own dating life. The science is sound, but how can she give her expert opinion with no real-world experience? In order to complete her doctoral thesis, she must crack the Sizzle Paradox - it seems the more sexually attractive she finds a guy, the less likely it is to come with an emotional connection; but why? - and to do that she must get the help she desperately needs. Kian Montgomery, her best friend, roommate, and fellow grad student, has no trouble bringing both romance and sizzle to his own relationships. When he offers to tutor Lyric on dating tactics to find a good match, she's certain it will solve her problems, and in exchange she agrees to set long-term-commitment-averse Kian up with someone different to give his romantic life a much-needed shakeup. But once the two progress with their "tutoring sessions," they start to feel less like the academic exercise they were supposed to be as real feelings develop. Which is a problem, because Lyric and Kian are best friends and absolutely, irrefutably nothing else... Right?"--